TRADISI AKADEMIK PESANTREN - Ahmad Shiddiq (TADRIS: Jurnal Pendidikan Islam, 2015)
Abstract: The learning  tradition in pesantren with all things, has different nuance to the tradition of learning outside the pesantren. Highly scientific tradition in pesantren creates students with the ability to master the Yellow Books (Classic Islamic Books) soon after graduating from the school, then, awarded a diploma from the Islamic Leader (Kia).  The students academic experience is a form of complete learning process, which can profile a figure of insightful, mature personality, and highly skilled graduates in conducting social engineering. Teaching the classic books is in the form of sorogan, Bandungan or weton, halakah and classroom discussion.  Keywords: academic tradition, system, school